2021
DOI: 10.1177/02683962211048201
|View full text |Cite
|
Sign up to set email alerts
|

Artificial intelligence and the conduct of literature reviews

Abstract: Artificial intelligence (AI) is beginning to transform traditional research practices in many areas. In this context, literature reviews stand out because they operate on large and rapidly growing volumes of documents, that is, partially structured (meta)data, and pervade almost every type of paper published in information systems research or related social science disciplines. To familiarize researchers with some of the recent trends in this area, we outline how AI can expedite individual steps of the literat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
65
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(67 citation statements)
references
References 104 publications
(190 reference statements)
1
65
0
1
Order By: Relevance
“…We find deeper insights into those articles to detect the diseases using advanced technology. While broader studies have already indicated healthcare and medical diagnosis adoption of different applications, none of them has focused on how to improve the literature review using a combination of traditional literature review and artificial intelligence (Kushwaha et al, 2021;Wagner et al, 2022;Xiao et al, 2018). This study endeavours to disclose to new and future researchers on how to conduct a smart literature investigation to obtain accurate insightful results.…”
Section: Contribution To the Theorymentioning
confidence: 99%
“…We find deeper insights into those articles to detect the diseases using advanced technology. While broader studies have already indicated healthcare and medical diagnosis adoption of different applications, none of them has focused on how to improve the literature review using a combination of traditional literature review and artificial intelligence (Kushwaha et al, 2021;Wagner et al, 2022;Xiao et al, 2018). This study endeavours to disclose to new and future researchers on how to conduct a smart literature investigation to obtain accurate insightful results.…”
Section: Contribution To the Theorymentioning
confidence: 99%
“…While a synthesis does include substantiation in terms of the validity of the associated relations, the student would be tasked to manually identify a derived synthesis or fuse a subset of candidate syntheses into a derived synthesis. That is, artificially smart technologies could supplement the manual natural intelligence of a researcher, replacing the traditional labor component of collecting, reading, comprehending, and synthesizing the manual literature review with a cognified one (Wagner et al, 2022). The combination would support deeper and richer research exploration.…”
Section: Cognification In Educationmentioning
confidence: 99%
“…Systematic reviews and meta-analyses are fundamental to supporting reproducibility and generalizability of research surrounding social and cultural aspects of human behavior, however, the process of extracting data from primary research is a labor-intensive effort, fraught with the potential for human error (see Pigott & Polanin, 2020;Yu et al, 2018). In contrast with the more defined standards that have evolved throughout the clinical research domain, within and across social sciences, substantial variation exists in research designs, reporting protocols, and even publication outlet standards (Davis et al, 2014;Short et al, 2018;Wagner et al, 2022). Notwithstanding that application of automation technologies in the social sciences could benefit from greater standardization of reporting protocols and terminology, understanding of the current state of (semi) automated extraction across these disciplines is largely speculative.…”
Section: Introductionmentioning
confidence: 99%